How does land use transformation coordinate with socioeconomic development in reservoir resettlement areas? Evidence from a Chinese town - Zhou, Kexin; Chen, Shaojun; Liang, Bing (Frontiers in Environmental Science, 2025)
Large-scale infrastructure projects often cause population displacement, creating challenges for land adaptation and socioeconomic integration in resettlement areas. This study examines Z Town, a reservoir-induced urbanized resettlement site in central China, using an improved Pressure–State–Response (PSR) framework to construct a multidimensional evaluation system. Results show that land use intensity (0.262) lags behind socioeconomic development (0.335), with institutional inertia and mismatches between land functions and residents’ needs as key barriers to coordination. This study contributes in two ways: 1) extending the PSR framework to resettlement research and providing a replicable tool for assessing land–society coupling; and 2) identifying land carrying capacity, resident satisfaction, and land allocation efficiency as critical constraints, offering practical entry points for policy. While based on a single case, the approach and findings are broadly applicable to dam resettlement, mining relocation, and ecological migration, underscoring the need to align land restructuring with human-centered development for sustainable and inclusive growth.